PERAN INOVASI PRODUK MEMEDIASI ORIENTASI PASAR TERHADAP KINERJA PEMASARAN PADA FASHION RETAIL DI KOTA DENPASAR - Julina, Made Mahayu; Kusuma, Anak Agung Gede Agung Artha (E-Jurnal Manajemen, 2017)
Increasing competition to compete for existing markets causes companies to establish the right strategy in marketing their business products. The study was conducted on several Fashion Retail in Denpasar City because so many Fashion Retail that developed rapidly, especially in Denpasar with the number of respondents as many as 100 people. The number of respondents is determined using purposive sampling. Data were obtained by distributing questionnaires analyzed using path analysis technique. Test results get market orientation effect posistif and significant to marketing performance, market orientation have positive and significant effect to product innovation, product innovation have positive and significant effect to marketing performance, product innovation variable can positively mediate significant market orientation to marketing performance. Limitations of this research is the scope of research that only includes Fashion Retail in the city of Denpasar alone so that the results of this study can not explain the state of the research area outside Fashion Retail Denpasar.